2019
DOI: 10.1097/md.0000000000014654
|View full text |Cite
|
Sign up to set email alerts
|

Change of HER2 status during disease recurrence predicts good prognosis for primary squamous cell carcinoma of the breast

Abstract: Rationale:Primary squamous cell carcinoma (PSCC) of the breast is one of the least common types of breast cancer. Adjuvant treatment for PSCC remains an unresolved issue.Patient concerns:We reported a case of a 48-year-old postmenopausal female patients with a 2 × 2.5 cm lump presented with no symptoms.Diagnoses:This patient was diagnosed as PSCC of the breast. The original tumor and first recurrence exhibited triple negative phenotype, whereas the second recurrence was HER2-positive.Interventions:A tumorectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…PSCC has no standard treatment (Yoneto et al, 2018;Alan et al, 2019;Cao et al, 2019;Lei and Miao, 2020). Squamous cell carcinoma of the breast is resistant to standard chemotherapy with IDC (cyclophosphamide, methotrexate, 5-FU, and adriamycin) (Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…PSCC has no standard treatment (Yoneto et al, 2018;Alan et al, 2019;Cao et al, 2019;Lei and Miao, 2020). Squamous cell carcinoma of the breast is resistant to standard chemotherapy with IDC (cyclophosphamide, methotrexate, 5-FU, and adriamycin) (Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This discordance is similar to the discrepancy in the ER, PR, and Her-2 statuses of the primary breast tumor and its distant metastatic foci, a well-documented phenomenon in breast cancer, which might also have an impact on treatment strategies. [3,31,32,33] Even though our study is limited by its small sample size and use of tissue microarrays instead of whole surface sections, we observed similar discordance in PD-L1 expressions of the primary tumor, lymph node, and distant metastasis, and our results were comparable to previous studies that reported the conversion of PD-L1 status in triple negative breast cancer patients [34] . Manson et al reported a PD-L1 (on tumor) discordance between primary tumors and matched distant metastases in 28.5% of the patients with breast cancer [35] .…”
Section: Discussionmentioning
confidence: 99%